2019
DOI: 10.1111/jne.12817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt loading on the organisation of microtubules in rat magnocellular vasopressin neurones

Abstract: Magnocellular vasopressin (VP) neurones are activated by increases in blood osmolality, leading to the secretion of VP into the circulation to promote water retention in the kidney, thus constituting a key mechanism for the regulation of body fluid homeostasis. However, chronic high salt intake can lead to excessive activation of VP neurones and increased circulating levels of VP, contributing to an elevation in blood pressure. Multiple extrinsic factors, such as synaptic inputs and glial cells, modulate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Super-resolution images obtained by structured illumination microscopy have revealed that MNCs contain many actin filaments and microtubules in their somata, with exclusive organization compared with cells in other brain regions, such as the cortex, as well as with hippocampal and other hypothalamic neurons ( Prager-Khoutorsky et al, 2014 ). Additionally, the density/array of actin filaments and microtubules are substantially changed in response to salt-loading ( Barad et al, 2020 ; Hicks et al, 2020 ), reinforcing the hypothesis that these elements participate in the mechanotransduction process. Based on the assumption that cytoskeleton components can redistribute forces across the lipid bilayer ( Ingber, 1997 ), Zhang et al (2007) proposed that osmosensory transduction depends on the amount and structure of F-actin filaments present in MNCs.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Super-resolution images obtained by structured illumination microscopy have revealed that MNCs contain many actin filaments and microtubules in their somata, with exclusive organization compared with cells in other brain regions, such as the cortex, as well as with hippocampal and other hypothalamic neurons ( Prager-Khoutorsky et al, 2014 ). Additionally, the density/array of actin filaments and microtubules are substantially changed in response to salt-loading ( Barad et al, 2020 ; Hicks et al, 2020 ), reinforcing the hypothesis that these elements participate in the mechanotransduction process. Based on the assumption that cytoskeleton components can redistribute forces across the lipid bilayer ( Ingber, 1997 ), Zhang et al (2007) proposed that osmosensory transduction depends on the amount and structure of F-actin filaments present in MNCs.…”
Section: Introductionmentioning
confidence: 54%
“…As we discuss in the coming sections, under chronic dehydration, the MNCs experience dramatic transcriptomic remodeling, which includes changes in the expression of several genes encoding plasma membrane channels and transporters ( Hindmarch et al, 2006 ; Greenwood M. P. et al, 2015 ; Johnson et al, 2015 ; Pauža et al, 2021 ). Another important adaptation is the increased complexity of the cytoskeleton array observed during sustained hyperosmolality ( Barad et al, 2020 ; Hicks et al, 2020 ), whose crucial role for osmosensitivity was previously demonstrated by Prager-Khoutorsky et al (2014) , also discussed later in this review. Thus, the new molecular phenotype of the MNCs under chronic osmotic challenge might also help understanding how they are able to ensure the continuous AVP and OXT secretion, essential for survival during dehydration, despite the incessant plasma membrane insertion due to the vesicle fusion.…”
Section: Introductionmentioning
confidence: 79%
“…Interestingly, Hicks et al demonstrated recently that the density of microtubules in magnocellular VP neurones increases in response to salt loading. The organisation of microtubules in other brain areas remains unchanged following salt loading, and only microtubule cytoskeleton in magnocellular SON and PVN neurones is modulated by this condition . Because an enhancement of microtubule density is sufficient to elevate the autonomous osmosensitivity of VP magnocellular neurones, the increase in microtubule density following salt loading can facilitate the activation of magnocellular VP neurones, contributing to excessive VP release and elevated blood pressure in this condition.…”
Section: Introductionmentioning
confidence: 97%
“…By contrast to actin filaments, which form a thin subcortical layer in these neurones, microtubules create a highly complex three‐dimensional network of filaments that occupy the entire cytoplasm of neuronal somata (Figure B). Super‐resolution imaging of microtubules in situ in different areas of the rodent brain revealed that magnocellular VP neurones from the SON and paraventricular nucleus (PVN) feature a unique microtubule structure that is strikingly different from the rectilinear microtubules commonly observed in other types of neurones, and from the typical pattern of centrosome‐divergent microtubules found in somatic cells . Thus, this interwoven microtubule network appears to be a unique feature of the magnocellular neurosecretory cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation